PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB HYPERTEXT MARKUP LANGUAGE (HTML) PADA MATAPELAJARAN EKONOMI MATERI BANK SENTRAL SISWA KELAS X IPS SMAN 1 GONDANGLEGI KABUPATEN MALANG SEMESTER GENAP TAHUN PELAJARAN 2017/2018 - Ibrahim Morteza Amin; Sapir Sapir (Jurnal Pendidikan Ekonomi, 2018)
With the development of the era, the technology also developed from smartphones to personal computers. This research is intended to develop teaching materials with HTML-based web browser on materials about economic materials Central Bank that can help students understand the material and facilitate teachers in evaluating the results of learning. The purpose of this research is as follows: (1) To develop the use of interactive economic learning media by using HTML web application for students of class X IPS 2 SMA Negeri 1 Gondanglegi Malang Regency on the material of central bank. (2) To know student response of class X IPS 2 SMA Negeri 1 Gondanglegi Malang Regency on economic learning media by using HTML web on central bank material.This research uses Borg and Gall model which has been adjusted to eight stages. Research development is a research method that is used to produce web media products and test the effectiveness of Web Media HTML-based. Data analysis techniques conducted in this study using qualitative and quantitative, Qualitative data in the comments from the later analysis in order to get input to the media and quantitative data obtained from the questionnaire validity related to the feasibility of HTML-based Web media whose data will be expressed in the form of numbers. Results of research and development of Web-Based Media HTML that applied to the students of class X IIS SMA Negeri 1 Gondanglegi Malang Regency can be shown with data from questionnaire validity that has been tested also to students. The result of the validation of Expert material is 93.18% and for the validity test of Expert Media by 86% while the result of the validity test to the student that is equal to 95.3% Thus, the results show that the learning media developed by the researcher is said to be very valid or very good. So for the next researchers and developers more innovative in developing HTML Web media in the Central Bank's learning process for the learning process easier.